Analytical and synthesized folklorism in Navoi’s work.: Journal of Contemporary Issues in Business and Government Vol. 27, No. 2,2021. https://cibg.org.au/ – pp. 1626-1633. - Rajabova, Marifat (FILOLOGIYA UFQLARI JURNALI, 2023)
Maqolada adabiyot shinoslikmasalari tahlil va taqdit qilingan